The feasibility of producing and utilising green hydrogen as a feedstock in Trinidad and Tobago - B. Hosein, Rointra; Balladin, Derrick; Alexander, David; Boodlal, Donnie; Bahaw, Edward; Maharaj, Rean (Universiti Teknologi MARA, Sarawak, 2025)
This study addresses Trinidad and Tobago's (TT) heavy reliance on grey hydrogen from Steam Methane Reforming (SMR), contributing significantly to CO2 emissions in the petrochemical sector. With rising hydrogen demand, especially for ammonia and methanol production, there is an imperative need to transition to green hydrogen. The study evaluates the economic feasibility of green hydrogen production in TT, assesses the potential impact on CO2 emissions, and analyses external factors such as subsidies, market dynamics, and the Carbon Border Adjustment Mechanism (CBAM). A combined quantitative and qualitative approach, incorporating cost modelling, sensitivity analyses, and environmental impact assessments, was used to evaluate economic viability and external influences. The analysis utilises secondary data from governmental and industry reports, including techno-economic models and GHG inventories calculated in accordance with the IPCC 2006 Guidelines. Findings indicate economic viability for green hydrogen under specific market conditions, significant CO2 mitigation potential, and opportunities for TT to establish a presence in the green hydrogen market. The impact of this transition could significantly reduce greenhouse gas (GHG) emissions, contributing to the nation's decarbonisation targets under its Nationally Determined Contributions (NDCs) while enabling economic diversification.